<< Chapter < Page Chapter >> Page >

1.1 definition: the z-transform x(z) of a causal discrete – time signal x(n) is defined as

X ( z ) = size 12{X \( z \) ={}} {} n = 0 x ( n ) z n size 12{ Sum cSub { size 8{n=0} } cSup { size 8{ infinity } } { size 11{x \( n \) }} z rSup { size 8{ - n} } } {} ( 4 . 1 ) size 12{ \( 4 "." 1 \) } {}

z is a complex variable of the transform domain and can be considered as the complex frequency. Remember index n can be time or space or some other thing, but is usually taken as time. As defined above , X ( z ) size 12{X \( z \) } {} is an integer power series of z 1 size 12{z rSup { size 8{ - 1} } } {} with corresponding x ( n ) size 12{x \( n \) } {} as coefficients. Let’s expand X ( z ) size 12{X \( z \) } {} :

X ( z ) = size 12{X \( z \) ={}} {} n = x ( n ) z n size 12{ Sum cSub { size 8{n= - infinity } } cSup { size 8{ infinity } } {x \( n \) z rSup { size 8{ - n} } } } {} = size 12{ {}={}} {} x ( 0 ) + x ( 1 ) z 1 + x ( 2 ) z 2 + . . . size 12{x \( 0 \) +x \( 1 \) z rSup { size 8{ - 1} } +x \( 2 \) z rSup { size 8{ - 2} } + "." "." "." } {} (4.2)

In general one writes

X ( z ) = size 12{X \( z \) ={}} {} Z [ x ( n ) ] size 12{Z \[ x \( n \) \] } {} (4.3)

In Eq.(4.1) the summation is taken from n = 0 size 12{n=0} {} to size 12{ infinity } {} , ie , X ( z ) size 12{X \( z \) } {} is not at all related to the past history of x ( n ) size 12{x \( n \) } {} . This is one–sided or unilateral z-transform . Sometime the one–sided z-transform has to take into account the initial conditions of x ( n ) size 12{x \( n \) } {} (see section 4.7).

In general , signals exist at all time , and the two-sided or bilateral z–transform is defined as

H ( z ) = size 12{H \( z \) ={}} {} n = h ( n ) z n size 12{ Sum cSub { size 8{n= - infinity } } cSup { size 8{ infinity } } {h \( n \) z rSup { size 8{ - n} } } } {}

= x ( 2 ) z 2 + x ( 1 ) z + x ( 0 ) + x ( 1 ) z 1 + x ( 2 ) z 2 + . . . size 12{ {}=x \( - 2 \) z rSup { size 8{2} } +x \( - 1 \) z+x \( 0 \) +x \( 1 \) z rSup { size 8{ - 1} } +x \( 2 \) z rSup { size 8{ - 2} } + "." "." "." } {} (4.4)

Because X ( z ) size 12{X \( z \) } {} is an infinite power series of z 1 size 12{z rSup { size 8{ - 1} } } {} , the transform only exists at values where the series converges (i.e. goes to zero as n size 12{n rightarrow infinity } {} or - size 12{ infinity } {} ). Thus the z-transform is accompanied with its region of convergence (ROC) where it is finite (see section 4.4).

A number of authors denote X + ( z ) size 12{X rSup { size 8{+{}} } \( z \) } {} for one-side z-transform.

Example 4.1.1

Find the z–transform of the two signals of Fig.4.1

Solution

(a) Notice the signal is causal and monotically decreasing and its value is just 0 . 8 n size 12{0 "." 8 rSup { size 8{n} } } {} for n 0 size 12{n>= 0} {} . So we write

x ( n ) = 0 . 8 n u ( n ) size 12{x \( n \) =0 "." 8 rSup { size 8{n} } u \( n \) } {}

and use the transform ( 4 . 1 ) size 12{ \( 4 "." 1 \) } {}

X ( z ) = size 12{X \( z \) ={}} {} n = 0 x ( n ) z n size 12{ Sum cSub { size 8{n=0} } cSup { size 8{ infinity } } {x \( n \) z rSup { size 8{ - n} } } } {}

= 1 + 0 . 8z 1 + 0 . 64 z 2 + 0 . 512 z 3 + . . . size 12{ {}=1+0 "." 8z rSup { size 8{ - 1} } +0 "." "64"z rSup { size 8{ - 2} } +0 "." "512"z rSup { size 8{ - 3} } + "." "." "." } {}

= 1 + ( 0 . 8z 1 ) + ( 0 . 8z 1 ) 2 + ( 0 . 8z 1 ) 3 + . . . size 12{ {}=1+ \( 0 "." 8z rSup { size 8{ - 1} } \) + \( 0 "." 8z rSup { size 8{ - 1} } \) rSup { size 8{2} } + \( 0 "." 8z rSup { size 8{ - 1} } \) rSup { size 8{3} } + "." "." "." } {}

Applying the formula of infinite geometric series which is repeated here

1 + a + a 2 + a 3 + . . . = size 12{1+a+a rSup { size 8{2} } +a rSup { size 8{3} } + "." "." "." ={}} {} n = 0 a n size 12{ Sum cSub { size 8{n=0} } cSup { size 8{ infinity } } {a rSup { size 8{n} } } } {} = 1 1 a size 12{ {}= { {1} over {1 - a} } } {} a < 1 size 12{ \lline a \lline<1} {} (4.5)

to obtain

X ( z ) = size 12{X \( z \) ={}} {} 1 1 0 . 8z 1 size 12{ { {1} over {1 - 0 "." 8z rSup { size 8{ - 1} } } } } {} = z z 0 . 8 size 12{ {}= { {z} over {z - 0 "." 8} } } {}

The result can be left in either of the two forms .

(b) The signal is alternatively positive and negative with increasing value .The signal is divergent . We can put the signal in the form

x ( n ) = ( 1 . 2 ) n 1 u ( n 1 ) size 12{x \( n \) = \( - 1 "." 2 \) rSup { size 8{n - 1} } u \( n - 1 \) } {}

which is ( 1 . 2 ) n u ( n ) size 12{ \( - 1 "." 2 \) rSup { size 8{n} } u \( n \) } {} delayed one index(sample) . Let’s use the transform ( 4 . 1 ) size 12{ \( 4 "." 1 \) } {}

X ( z ) = size 12{X \( z \) ={}} {} n = 0 x ( n ) z n size 12{ Sum cSub { size 8{n=0} } cSup { size 8{ infinity } } {x \( n \) z rSup { size 8{ - n} } } } {}

= 0 + 1 . 0 ( z 1 ) 1 . 2 ( z 1 ) 2 + 1 . 44 ( z 1 ) 3 1 . 718 ( z 1 ) 4 + . . . size 12{ {}=0+1 "." 0 \( z rSup { size 8{ - 1} } \) - 1 "." 2 \( z rSup { size 8{ - 1} } \) rSup { size 8{2} } +1 "." "44" \( z rSup { size 8{ - 1} } \) rSup { size 8{3} } - 1 "." "718" \( z rSup { size 8{ - 1} } \) rSup { size 8{4} } + "." "." "." } {}

= z 1 [ 1 + ( 1 . 2z 1 ) + ( 1 . 2z 1 ) 2 + ( 1 . 2z 1 ) 3 + . . . ] size 12{ {}=z rSup { size 8{ - 1} } \[ 1+ \( - 1 "." 2z rSup { size 8{ - 1} } \) + \( - 1 "." 2z rSup { size 8{ - 1} } \) rSup { size 8{2} } + \( - 1 "." 2z rSup { size 8{ - 1} } \) rSup { size 8{3} } + "." "." "." \] } {}

= z 1 1 1 + 1 . 2z 1 = z 1 1 + 1 . 2z 1 = 1 z + 1 . 2 size 12{ {}=z rSup { size 8{ - 1} } { {1} over {1+1 "." 2z rSup { size 8{ - 1} } } } = { {z rSup { size 8{ - 1} } } over {1+1 "." 2z rSup { size 8{ - 1} } } } = { {1} over {z+1 "." 2} } } {}

1.2 the inverse z-transform

The inverse z-transform is denoted by Z 1 size 12{Z rSup { size 8{ - 1} } } {} :

x ( n ) = Z 1 [ X ( z ) ] size 12{x \( n \) =Z rSup { size 8{ - 1} } \[ X \( z \) \] } {} (4.6)

The signal x ( n ) size 12{x \( n \) } {} and its transform constitutes a transform pair

X ( n ) Z ( z ) size 12{X \( n \) ↔Z \( z \) } {} (4.7)

One way to find the inverse transform , whenever possible , is to utilize just the z-transform definition. General methods of the inverse z-transform are discursed in section 4.5 and 4.6

Example 4.1.2

Find the inverse z-transform of the following

  1. X ( z ) = size 12{X \( z \) ={}} {} z z 0 . 8 size 12{ { {z} over {z - 0 "." 8} } } {}
  2. 1 z + 1 . 2 size 12{ { {1} over {z+1 "." 2} } } {}

Solution

(a) Let’s write

X ( z ) = size 12{X \( z \) ={}} {} z z- 0 . 8 size 12{ { {z} over {"z-"0 "." 8} } } {} = size 12{ {}={}} {} 1 1 0 . 8z 1 size 12{ { {1} over {1-0 "." 8z rSup { size 8{-1} } } } } {}

= 1 + ( 0 . 8z 1 ) + ( 0 . 8z 1 ) 2 + ( 0 . 8z 1 ) 3 + . . . size 12{ {}=1+ \( 0 "." 8z rSup { size 8{ - 1} } \) + \( 0 "." 8z rSup { size 8{ - 1} } \) rSup { size 8{2} } + \( 0 "." 8z rSup { size 8{ - 1} } \) rSup { size 8{3} } + "." "." "." } {}

= 1 + 0 . 8z 1 + 0 . 64 z 2 + 0 . 512 z 3 + . . . size 12{ {}=1+0 "." 8z rSup { size 8{ - 1} } +0 "." "64"z rSup { size 8{ - 2} } +0 "." "512"z rSup { size 8{ - 3} } + "." "." "." } {}

By comparing term by term with Equation ( 4 . 2 ) size 12{ \( 4 "." 2 \) } {} we get

x ( n ) = [ 1,0 . 8,0 . 64 , 0 . 512 ; . . . ] size 12{x \( n \) = \[ 1,0 "." 8,0 "." "64",0 "." "512"; "." "." "." \] } {}

or

x ( n ) = size 12{x \( n \) ={}} {} 0 . 8 n u ( n ) size 12{0 "." 8 rSup { size 8{n} } u \( n \) } {}

(b) Let’s write

X ( z ) = size 12{X \( z \) ={}} {} 1 z + 1,2 size 12{ { {1} over {z+1,2} } } {} = z 1 1 + 1,2 z 1 size 12{ {}= { {z rSup { size 8{ - 1} } } over {1+1,2z rSup { size 8{ - 1} } } } } {} = z 1 1 1 + 1,2 z 1 size 12{ {}=z rSup { size 8{ - 1} } { {1} over {1+1,2z rSup { size 8{ - 1} } } } } {}

Next , let’s expand X ( z ) size 12{X \( z \) } {} :

X ( z ) size 12{X \( z \) } {} = z 1 [ 1 + ( 1 . 2z 1 ) + ( 1 . 2z 1 ) 2 + ( 1 . 2z 1 ) 3 + . . . ] size 12{ {}=z rSup { size 8{ - 1} } \[ 1+ \( - 1 "." 2z rSup { size 8{ - 1} } \) + \( - 1 "." 2z rSup { size 8{ - 1} } \) rSup { size 8{2} } + \( - 1 "." 2z rSup { size 8{ - 1} } \) rSup { size 8{3} } + "." "." "." \] } {}

= 0 + 1 . 0z 1 1 . 2z 2 + 1 . 44 z 3 1 . 728 z 4 + . . . size 12{ {}=0+1 "." 0z rSup { size 8{ - 1} } - 1 "." 2z rSup { size 8{ - 2} } +1 "." "44"z rSup { size 8{ - 3} } - 1 "." "728"z rSup { size 8{ - 4} } + "." "." "." } {}

Thus

x ( n ) = [ 0,1 . 0, 1 . 2,1 . 44 , 1 . 728 , . . . ] size 12{x \( n \) = \[ 0,1 "." 0, - 1 "." 2,1 "." "44", - 1 "." "728", "." "." "." \] } {}

or

x ( n ) = ( 1 . 2 ) n 1 u ( n 1 ) size 12{x \( n \) = \( - 1 "." 2 \) rSup { size 8{n - 1} } u \( n - 1 \) } {}

That is

x ( n ) = 0 size 12{x \( n \) =0} {} n 0 size 12{n<= 0} {}

Questions & Answers

the definition for anatomy and physiology
Watta Reply
what is microbiology
Agebe Reply
What is a cell
Odelana Reply
what is cell
Mohammed
how does Neisseria cause meningitis
Nyibol Reply
what is microbiologist
Muhammad Reply
what is errata
Muhammad
is the branch of biology that deals with the study of microorganisms.
Ntefuni Reply
What is microbiology
Mercy Reply
studies of microbes
Louisiaste
when we takee the specimen which lumbar,spin,
Ziyad Reply
How bacteria create energy to survive?
Muhamad Reply
Bacteria doesn't produce energy they are dependent upon their substrate in case of lack of nutrients they are able to make spores which helps them to sustain in harsh environments
_Adnan
But not all bacteria make spores, l mean Eukaryotic cells have Mitochondria which acts as powerhouse for them, since bacteria don't have it, what is the substitution for it?
Muhamad
they make spores
Louisiaste
what is sporadic nd endemic, epidemic
Aminu Reply
the significance of food webs for disease transmission
Abreham
food webs brings about an infection as an individual depends on number of diseased foods or carriers dully.
Mark
explain assimilatory nitrate reduction
Esinniobiwa Reply
Assimilatory nitrate reduction is a process that occurs in some microorganisms, such as bacteria and archaea, in which nitrate (NO3-) is reduced to nitrite (NO2-), and then further reduced to ammonia (NH3).
Elkana
This process is called assimilatory nitrate reduction because the nitrogen that is produced is incorporated in the cells of microorganisms where it can be used in the synthesis of amino acids and other nitrogen products
Elkana
Examples of thermophilic organisms
Shu Reply
Give Examples of thermophilic organisms
Shu
advantages of normal Flora to the host
Micheal Reply
Prevent foreign microbes to the host
Abubakar
they provide healthier benefits to their hosts
ayesha
They are friends to host only when Host immune system is strong and become enemies when the host immune system is weakened . very bad relationship!
Mark
what is cell
faisal Reply
cell is the smallest unit of life
Fauziya
cell is the smallest unit of life
Akanni
ok
Innocent
cell is the structural and functional unit of life
Hasan
is the fundamental units of Life
Musa
what are emergency diseases
Micheal Reply
There are nothing like emergency disease but there are some common medical emergency which can occur simultaneously like Bleeding,heart attack,Breathing difficulties,severe pain heart stock.Hope you will get my point .Have a nice day ❣️
_Adnan
define infection ,prevention and control
Innocent
I think infection prevention and control is the avoidance of all things we do that gives out break of infections and promotion of health practices that promote life
Lubega
Heyy Lubega hussein where are u from?
_Adnan
en français
Adama
Got questions? Join the online conversation and get instant answers!
Jobilize.com Reply

Get Jobilize Job Search Mobile App in your pocket Now!

Get it on Google Play Download on the App Store Now




Source:  OpenStax, Z-transform. OpenStax CNX. Jul 29, 2009 Download for free at http://cnx.org/content/col10798/1.1
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Z-transform' conversation and receive update notifications?

Ask